Electromagnetic Forces in Electroactive Polymers - Aczél, Á. (Acta Technica Jaurinensis, 2012)
This paper reviews the equations that govern the hyperelastic deformations of magnetosensitive and electroactive materials in the presence of electromagnetic field. These relations can be derived from the Maxwellequations and some fundamental thermodynamical and continuum mechanical theorems. The aim of this paper is to estimate the terms in the governing equations for defining their order of magnitude in case of common EAP actuators.